2014
DOI: 10.1097/ccm.0b013e31829e53dc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propofol on Patient-Ventilator Synchrony and Interaction During Pressure Support Ventilation and Neurally Adjusted Ventilatory Assist*

Abstract: In pressure support ventilation, deep propofol sedation increased asynchronies, while light sedation did not. Propofol reduced the respiratory drive, while breathing timing was not significantly affected. Gas exchange and breathing pattern were also influenced by propofol infusion to an extent that varied with the depth of sedation and the mode of ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 38 publications
7
109
0
1
Order By: Relevance
“…These two calibration approaches to compare absolute values of a patient's effort obtained from EAdi require further validation. It is also important to note that EAdi amplitude can be influenced by other factors, such as sedation [75] and clinical evolution [74].…”
Section: The Correlation Between Diaphragm Electrical Activity and Pementioning
confidence: 99%
See 1 more Smart Citation
“…These two calibration approaches to compare absolute values of a patient's effort obtained from EAdi require further validation. It is also important to note that EAdi amplitude can be influenced by other factors, such as sedation [75] and clinical evolution [74].…”
Section: The Correlation Between Diaphragm Electrical Activity and Pementioning
confidence: 99%
“…EAdi can also be used to accurately monitor patientventilator synchrony [55,75,76]. Finally, as the EAdi value recorded at the onset of the inspiratory flow (autoEAdi) is tightly correlated with the patient's auto-PEEP, as measured by Pes [77], EAdi can also be used to estimate auto-PEEP.…”
Section: The Correlation Between Diaphragm Electrical Activity and Pementioning
confidence: 99%
“…By adopting EAdi monitoring, Vaschetto et al [18] showed in intubated patients that propofol significantly interferes with patient-ventilator synchrony in pressure support ventilation (PSV) at doses producing deep sedation. Both during PSV and neurally adjusted ventilator assistance (NAVA), propofol reduced neural drive and effort, while not significantly affecting respiratory timing.…”
Section: Dangerous Side Effects Of Sedationmentioning
confidence: 99%
“…As depicted in Fig. 2, during partial ventilatory assistance, EAdi is influenced by multiple factors, including the amount of assistance and sedation [4,5 && ]. With NAVA and PAV, the mechanical support delivered by the ventilator is directly (NAVA) or indirectly (PAV) driven and regulated by the effort exerted by the respiratory muscles [2]; this does not occur with the other assisted modes, in which the mechanical support is not affected by the patient's drive and effort.…”
Section: Respiratory Drive and Effortmentioning
confidence: 99%